Reencantamento digital? : a internet como ferramenta de poder da igreja - Lambert, Karina Inácio de Araujo (2017)
The history of humanity is marked by religion. Assuming the status of bridge between gods and men, religious institutions succeeded in maintaining, for centuries, relations of power as holders of religious knowledge, considered as unquestionable. In this way, their influence has unfolded on different fronts, becoming a social phenomenon that leads to behaviors, opinions and directs actions, often of entire societies. Until the rationality characteristic of modernity, driven by capitalism and Enlightenment thought, fragmented the religious world, provoking what Max Weber (2004) calls disenchantment. At that moment religion lost its hegemony as a producer of meaning, becoming a subjective choice. However, the pace and accelerated changes promoted by information technology have breathed new life into religion, but not without causing profound changes. From then on, there is the "unfolding of an individual, mobile and moldable religiosity that gives way to new forms of religious sociability" (HERVIEULÉGER, 2015, p.30). The media become a two-way street, for they both allow for a reenchantment by religion, and they bring about a shake-up in the authority of institutions, since they are no longer the sole holders of religious knowledge. Thus, this research seeks to approach the religious panorama of our time from the constant movement of religious institutions to maintain their authority and power relations, often manipulating the sacred in pursuit of social, political, and economic interests in a control society in which Power and institutions are crossed by the message of communication.